2014
DOI: 10.1091/mbc.e13-04-0219
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of multicellular differentiation inDictyostelium discoideumis regulated by coronin A

Abstract: Multicellular development of Dictyostelium is induced by starvation and is crucial for its long-term survival. Coronin A mediates the transition from growth to development of the cells and initiates the cAMP-dependent relay by regulating the response to secreted cell density and nutrient deprivation factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 78 publications
3
43
0
Order By: Relevance
“…Coronin levels were therefore analyzed (Figure B). Coronin was already increased in control cells, probably because coronin is mandatory for initiation of cAMP pulsing upon starvation in a serum‐free medium . Nicotine does not seem to increase, but rather it decreases coronin levels.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Coronin levels were therefore analyzed (Figure B). Coronin was already increased in control cells, probably because coronin is mandatory for initiation of cAMP pulsing upon starvation in a serum‐free medium . Nicotine does not seem to increase, but rather it decreases coronin levels.…”
Section: Resultsmentioning
confidence: 93%
“…Coronin was already increased in control cells, probably because coronin is mandatory for initiation of cAMP pulsing upon starvation in a serum-free medium. 45 Nicotine does not seem to increase, but rather it decreases coronin levels. Therefore, at least in our model, increase in cofilin activity in nicotine-stimulated cells does not seem to be linked to coronin or to ERK activity.…”
Section: Melatonin Counteracts Cofilin Phosphorylation and Reduces mentioning
confidence: 96%
“…However, very recently, the importance of coronins in signaling pathways has been revealed. The mammalian neural coronin 1 and the more primitive Dictyostelium coronin A play important, notably F‐actin‐independent roles in cAMP signaling (76, 77). Mouse coronin 6, which is the closest mammalian homologue to TgCOR, participates in the clustering of acetylcholine receptors at the postsynaptic membrane (78).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we describe an essential role for coronin 1 in allograft rejection via the modulation of the phosphodiesterase 4-CREB-CaMKIV pathway in T cells. We found that coronin 1 maintains appropriate levels of cAMP, similar to its role in regulating the cAMP-protein kinase A pathway in neurons and Dictyostelium (via its ortholog coronin A, Jayachandran et al, 2014;Vinet et al, 2014). Suppression was specific for alloresponses, since infection-mediated CD28 ligation through CD80 could overcome cAMP-mediated suppression of T cell responses.…”
Section: Introductionmentioning
confidence: 55%